Influence of compost application rate on nutrient and heavy metal mobility: Implications for stormwater management. Issue 6 (20th September 2022) - Kranz, Christina N.; Rivers, Erin N.; McLaughlin, Richard A.; Heitman, Joshua L.
Abstract: Amending soils with compost has become increasingly common in stormwater management practices. Compost can be a source and sink for nutrients and heavy metals, and it is important to understand the effect of compost on pollutant leaching under different hydrologic conditions. The objectives of this study were (a) to quantify the distribution coefficient ( K d ) of PO4 –P and metals (Cd, Cr, Cu, Ni, Pb, Zn) for compost–soil blends and (b) to examine how compost rate alters leaching patterns of nutrients (NH4 –N, NO3 –N, PO4 –P) and metals from compost–soil blends. Material consisted of a sandy loam subsoil, a yard‐waste compost, and compost–soil blends at 20 or 50% compost by volume. Materials were tested in sorption–desorption experiments using simulated stormwater (SW); columns with the materials were also leached with either SW or deionized (DI) water. As compost rate increased, the K d decreased for PO4 –P and Cr but increased for Cd, Cu, Ni, and Zn. The addition of compost reduced the sorption of PO4 –P and Cr, potentially making it a source of these pollutants. Simulated stormwater did not increase the amount of pollutants retained compared with DI water for compost blends, except for 100% compost columns. Nitrate was the only constituent that had a negative removal efficiency, suggesting the compost was a source of NO3 –N. Column media retained >70% of the metals from the added stormwater solution. These results suggest that yard‐waste compost blends at ≤50% have the potential to retain certain pollutants from infiltrating stormwater, but this effect may decline after several storm events. Core Ideas: Compost–soil blends were dosed with stormwater to measure pollutant leaching and retention. Increasing compost rates increased mobility (reduced K d ) of phosphate and chromium. Simulated stormwater inputs did not increase leaching of pollutants compared with DI water. Compost influences pollutant transport and may retain most metals when infiltrating stormwater.